Accurate Location of Catheter Tip With the Free-to-Total Metanephrine Ratio During Adrenal Vein Sampling - Christou, Foteini; Pivin, Edward; Denys, Alban; Abid, Karim A.; Zingg, Tobias; Matter, Maurice; Pechère-Bertschi, Antoinette; Maillard, Marc; Grouzmann, Eric; Wuerzner, Gregoire (Frontiers in Endocrinology, 2022)
Background The selectivity index (SI) of cortisol is used to document correct catheter placement during adrenal vein sampling (AVS) in patients with primary aldosteronism (PA). We aimed to determine the cutoff values of the SIs based on cortisol, free metanephrine, and the free-to-total metanephrine ratio (FTMR) using an adapted AVS protocol in combination with CT. Methods Adults with PA and referred for AVS were recruited in two hypertension centers. The cortisol and free metanephrine-derived SIs were calculated as the concentration of the analyte in adrenal veins divided by the concentration of the analyte in the distal vena cava. The FTMR-derived SI was calculated as the concentration of free metanephrine in the adrenal vein divided by that of total metanephrine in the ipsilateral adrenal vein. The AVS was classified as an unequivocal radiological success (uAVS) if the tip of the catheter was seen in the adrenal vein. The SI cutoffs of each index marker were established using receiver operating characteristic curve analysis. Results Out of 125 enrolled patients, 65 patients had an uAVS. The SI cutoffs were 2.6 for cortisol, 10.0 for free metanephrine, 0.31 for the FTMR on the left side, and 2.5, 9.9, and 0.25 on the right side. Compared to free metanephrine and the FTMR, cortisol misclassified AVS as unsuccessful in 36.6% and 39.0% of the cases, respectively. Conclusion This study is the first to calculate the SIs of cortisol, free metanephrine, and the FTMR indices for the AVS procedure. It confirms that free metanephrine-based SIs are better than those based on cortisol.